Two classes of reconfigurable parallel mechanisms constructed with multi-diamond kinematotropic chain. (November 2016) - Ye, Wei; Fang, Yuefa; Guo, Sheng; Chen, Yaqiong
This paper presents a novel multi-diamond kinematotropic chain that has various motion branches. The motion allowed by the chain in different branches is identified based on Lie group theory. A planar reconfigurable limb is obtained by adding a prismatic joint to the output link of the multi-diamond kinematotropic chain, leading to the construction of a class of planar reconfigurable parallel mechanisms. With the multi-diamond kinematotropic chain evolving into different motion branches, the planar reconfigurable mechanisms have three distinct configurations in which different operation modes including the 2T1R mode, 2T mode and 1T1R mode can be carried out. The multi-diamond kinematotropic chain is also integrated in the design of spatial reconfigurable limbs, resulting in the construction of a class of spatial reconfigurable parallel mechanisms with ten mobility configurations.